Artificial Intelligence Verification Platform using Block Chain with Distributed Ledger Technology (International Journal of Innovative Research in Computer Science & Technology, 2021)
Developments in (AI) or (DLT) are now  provoking lively debate in practice and academia. AI uses  data to achieve goals that were previously believed to be  only possible for humans. In an unsettled context,  distributed ledger technology has the potential to establish  consensus about information among a group of  contributors. Both technologies that are needed in similar  and common systems are investigated in this study. As a  result, the safe pattern (DLT) or the creation of a federated  learning system spread over many nodes. It has the ability  to lead technological convergence, which has previously  covered the technique for the major revolution in  technology (IT). Earlier work summarizes many possible  benefits of the convergence of DLT and AI, but only  provides a limited theoretical framework to describe future  real-world DLT and AI merger instances. The primary goal  of this research is to disseminate by maintaining systematic  previous works and offering conscientious derivative future  research opportunities. This study contributes to  overcoming existing constraints in AI and DLT  convergence for both technologies.
Keywords: Artificial Intelligence; BlockChain; Distributed Ledger Technology; nformation Technology; Verification